Social Innovations between Politics and Policy - Lyubomirova, Veselina (UNWE Yearbook, 2021)
The Social innovations are a trendy approach for presenting modern ideas in management and policy plans especially at the local and regional levels. It is also a well-adopted concept on the national level mainly in the social policy, and partly in some economic development measures. The understanding of their role, place, and capacity in the contemporary and future governance mix of instruments is an area open to debate. Where do social innovations stand between politics for social change and the policy for social problem-solving? What is their specific implementation in the social sector and policy? These are the main questions that this piece of research addresses. The results expose two different understandings and approaches to the development and implementation of social innovations. The presented conclusions are useful in reconsidering the social or societal variety of innovations at the policy level.
Keywords: Social innovation; Social changes; Social transformation; Societal innovations; Social entrepreneurship